Essentials of pathophysiology : concepts of altered health states - Porth, Carol; Gaspard, Kathryn J. (Philadelphia : Wolters Kluwer, 2015)
A student-friendly text that delivers "need to know" disease content, along with the essential foundation in science that nursing, physician assistant, pharmacology, advanced health science, and medical students need to succeed in their future careers.
Cell and tissue function -- Integrative body functions -- Hematopoietic function -- Infection and immunity -- Circulatory function -- Respiratory function -- Kidney and urinary tract function -- Gastriontestinal and hepatobiliary -- Endocrine systems -- Nervous systems -- Genitourinary and reproductive function -- Musculoskeletal fuction -- Integumentray function
Includes bibliographical references and index.
Keywords: Disease -- Nurses' Instruction; Pathologic Processes -- Nurses' Instruction; Physiological Phenomena -- Nurses' Instruction